KNOWLEDGE AND ATTITUDE OF ELEMENTARY SCHOOL CHILDREN REGARDING COVID-19 - Arif Rohman Mansur; Ira Mulya Sari; Yelly Herien; Meri Neherta; Miftahul Ilmi; Aditya Yudha Pradhana (UPT Penerbitan Universitas Jember, 2020)
Background: The COVID-19 pandemic around the world puts children at risk of becoming the most prominent victims. Children usually have less ability to decipher and understand the content of the news about the COVID-19 outbreak. Assessment of elementary school children's knowledge and attitudes is critical in identifying gaps, strengthening prevention efforts, and overcoming the epidemic. Purpose This study was aimed to describe and assess elementary school children's knowledge and attitudes about COVID-19, signs and symptoms, modes of transmission, precautions, and attitudes towards COVID-19. Methods This research was used a cross-sectional design to describe knowledge and attitude of elementary school children. The cluster sampling technique was used to recruit 92 of children aged 7-12 years. An online questionnaire was posted through WhatsApp group questionnaire that developed by the author to measure knowledge and attitudes towards COVID-19 based on literature. The instrument was declared valid and reliable with Cronbach alpha 0.71, consisting of four main parts: socio-demographics, sources of information, knowledge, and attitudes of primary school children regarding COVID-19. Data analysis used descriptive statistics, percentage, and frequency for grouped measurements. Results: The majority of children get COVID-19 information from social media and family/friends (62.4%), knowing about COVID-19 (59.9%), mode of transmission (88%), signs and symptoms (47.8%), prevention (78.4%), and protective attitudes against COVID-19 (58.3%). Conclusion The insufficient understanding still become a problem of school aged children regarding the symptoms of COVID-19 and the lack of attitudes of elementary school children towards self-protection against COVID-19 that potential for increasing the transmission of COVID-19 infection to children. Nurses as educators could provide health education to improve elementary school students' understanding of signs of symptoms and attitudes for protecting against COVID-19 through a learning by playing approach Keywords: COVID-19; Knowledge; Attitude; School age Children.